A collection of artefacts made from boar tusks. From the trypillia culture settlement at „Berezovskaya Ges” - Hrytsiuta, Oksana; Siekerska, Olena (Acta Archaeologica Lodziensia, 2022)
The aim of this paper is to present to the academic community previously unpublished materials from the excavation of a settlement at «Berezovskaya GES» belonging to the Trypillia culture, located in the forest-steppe Bug region. The group of materials under study is а collection of tools made from wild boar tusk. The assembly comprises a large number of tools with varying degrees of use-wear, among them are preforms, blanks and debris. The tools underwent technical, morphological and traceological studies with the results being discussed in the article.